Helical stent (SUPERA™) and drug-coated balloon (Passeo–18 Lux™) for recurrent cephalic arch stenosis: Rationale and design of arch V SUPERA–LUX Study. Issue 4 (July 2020) - Tang, TY; Tan, CS; Yap, CJQ; Tan, RY; Tay, HH; Choke, ETC; Chong, TT
Background: The treatment options for cephalic arch stenosis are limited and standard of care remains at crossroads – none are ideal and there is currently no gold standard. Endovascular techniques are now the preferred primary therapeutic option because they are minimally invasive and better tolerated by haemodialysis patients who have multiple comorbidities. However, conventional plain old balloon angioplasty, bare metal stenting and stent grafts all have their limitations. The aim of this trial is to evaluate whether the helical SUPERA™ stent (Abbott Vascular, Santa Clara, CA, USA), which has a higher degree of flexibility and resistance to compressive forces compared to traditionally laser-cut nitinol stents, combined with a drug-coated balloon (Biotronik Passeo-18 Lux™) to minimize the neointimal hyperplasia effect, can improve patency and reduce reintervention rates. Methods and results: Arch V SUPERA-LUX is a pilot investigator-initiated single-centre, single-arm prospective study. Twenty patients with a brachiocephalic fistula within 6 months of initial plain old balloon angioplasty for significant cephalic arch stenosis will be recruited for treatment with SUPERA and drug-coated balloon. The primary objectives are immediate angiographic and procedural success, primary patency and functional fistula at 1 week, 8 weeks, 6 and 12 months. The results from eight patients treated prospectively as proof of concept have shown primary patency of 83.3% at 1 year with 100% technical and procedural success rates. Enrolment for the Arch V SUPERA-LUX study is expected to be completed at the end of 2019. Conclusion: The Arch V SUPERA-LUX study is the first trial to evaluate whether SUPERA stent implantation and drug-coated balloon use can provide superior protection against restenosis compared to traditional angioplasty, bare metal stents and stent grafts in recurrent cephalic arch stenosis. Initial pilot results are encouraging but longer follow-up is required to truly test this technique. Trial registration: This study is registered on ClinicalTrials.gov NCT03891693.